Under Cover of Science American Legal-Economic Theory and the Quest for Objectivity - Hackney, James R., 1964- (Book collections on Project MUSE., 2007)
A critique of the Law & Economics movement, this book draws connections between conceptions of science and efforts at legitimating American legal theory as an objective enterprise.